(untitled) (Abdimas Medika, 2025)
Community service is carried out through a health promotion course at SMK Negeri This community service aims to increase awareness and knowledge about early detection of breast cancer through the breast self-examination method (SADARI) at SMK Negeri 17 Samarinda. Breast cancer is one of the diseases with the highest mortality rate among women, so early detection is very important to increase the chances of recovery. This activity includes counseling and practical training on SADARI to students at SMK Negeri 17. The methods used are interactive lectures, demonstrations, and discussions to provide a better understanding of the importance of early detection of breast cancer. Evaluation was conducted through pre-test and post-test to measure changes in participants’ knowledge before and after the activity. The results of the activity showed a significant increase in students’ knowledge of breast cancer and the SADARI procedure as evidenced by the students’ active participation during the practical sessions as well as their enthusiasm for the importance of early detection. Thus, this community service recommends that similar activities be implemented in a sustainable manner and made part of the health education curriculum in schools, to support breast cancer early detection efforts among adolescents